Competition of beta-lactam antibiotics for the penicillin-binding proteins of Neisseria gonorrhoeae. - Dougherty, T J (1981)
The affinities of nine structurally different beta-lactam antibiotics for the three major gonococcal penicillin-binding proteins (PBPs) were determined by using a competition assay with tritium-labeled penicillin and live, growing bacteria. Each determination was carried out in parallel in isogenic pairs of penicillin-susceptible (minimal inhibitory concentration of penicillin, 0.0075 microgram/ml) and intrinsically penicillin-resistant (minimal inhibitory concentration of penicillin, 0.5 microgram/ml) cells. Evidence is presented indicating that (i) PBP 3 may be a dispensable function; (ii) acquisition of resistance is accompanied by change in the beta-lactam antibiotic affinities of PBP 2 but not of PBP 1; (iii) PBP 2 appears to be the most important physiological target in the penicillin-susceptible strain; in the penicillin-resistant strain, PBP 1 seems to assume this role. The relative affinities of various beta-lactam antibiotics for the individual PBPs showed substantial variation with the antibiotic structure.